(untitled) (Journal of Paediatric Surgeons of Bangladesh, 2013)
Background: Hydronephrosis in children is a common abnormality of the kidney. Surgical intervention in patient with hydronephrosis is to improve urinary drainage and to preserve renal function. Surgery (Anderson Hynes pyeloplasty: A-H pyeloplasty ) can be done with or without (Nephrostomy tube) D-J stent.Here we are describing our comparative experience between A-H pyeloplasty with D-J stent and A-H pyeloplasty with nephrostomy tube, at Bangabandhu Sheikh Mujib Medical University(BSMMU) to show the postoperative advantages of the former over the latter. Objectives: To assess functional outcome after A-H pyeloplasty with or without D-J stent in patients of unilateral hydronephrosis. Post operatively renal function was estimated after 3 months by DTPA renogram. Methods: It was a prospective study at Paediatric Surgery department of Bangabandhu Sheikh Mujib Medical University from April 2009 to October 2010. Twenty eight ( age, sex, side and type of operation matched) patients of unilateral hydronephrosis were included in the study and divided into two Groups: Group A (na =15) and Group B (nb=13) patients who underwent A-H pyeloplasty with D-J stent and A-H pyeloplasty with nephrostomy tube respectively. Child with bilateral hydronephrosis, hydronephrosis with associated anomalies like horseshoe kidney, ectopic kidney, solitary kidney, hydronephrosis with vesico ureteric reflux and redopyeloplasty were excluded in this study. Unpaired t test and Chi-square test were used for statistical analysis whereas postoperative hospital stay and renal functional improvement were used as parameters of the study. Results: For study Group A (A-H pyeloplasty with D-J stent) postoperative hospital stay were significantly lesser (P<0.00) than the GroupB ( A-H pyeloplasty with nephrostomy tube). Post operative split renal function and glomerular filtration rate (GFR) in Group A was improved (percentage) than Group B. Conclusion: This study reveals postoperative shorter hospital stay and improved postoperative split renal function in A-H pyeloplasty with D-J stent. DOI: http://dx.doi.org/10.3329/jpsb.v2i1.15159 Journal of Paediatric Surgeons of Bangladesh (2011) Vol. 2 (1): 22-25